Geochemistry of serpentine muds of ODP Leg 125 holes - Heling, Dietrich; Schwarz, Alexander (Supplement to: Heling, D; Schwarz, A (1992): Iowaite in serpentinite muds at Sites 778, 779, 780, and 784: a possible cause for the low chlorinity of pore waters. In: Fryer, P; Pearce, JA; Stokking, LB; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 125, 313-323, https://doi.org/10.2973/odp.proc.sr.125.176.1992, 1992)
The <63-µm fractions of serpentinite muds from two seamounts on the Mariana and Izu-Bonin forearcs were analyzed for mineral composition by X-ray diffraction and for chemical composition by X-ray fluorescence. The silt fraction of the muds consists predominantly of chrysotile, brucite, and ample amorphous constituents. Chlorite and smectite are less abundant components. Of special interest is the occurrence of iowaite, a brucite-like, Cl-bearing mineral with a layered structure. Iowaite was not found in the samples from the summit site of one of the seamounts drilled; however, it is scattered throughout the strata, composing the flanks of both seamounts investigated. No systematic change of the iowaite abundance with depth was observed. The distribution of iowaite is confined to the surface of the flanks of the seamount. Based on the distribution on the mineral and its chemical composition, we suggest that the iowaite formed by oxidation of some of the ferrous iron in brucite contained in the serpentine mud as it contacted abyssal seawater during protrusion onto the seafloor. The resulting positive charge imparted to the brucite was compensated by the uptake of seawater chloride. Consequently, the formation of iowaite is restricted to the seafloor where oxygen and chloride are available for these reactions. The availability of oxygen is considered the limiting factor. We conclude that iowaite formation cannot be a major cause for the low chlorinity of pore fluids inside the seamounts.